Autophagy in Human T-Cell Leukemia Virus Type 1 (HTLV-1) Induced Leukemia - Ducasa, Nicolás (Front Oncol, 2021)
Viruses play an important role in the development of certain human cancers. They are estimated to contribute 16% to all human cancers. Human T-cell leukemia virus type 1 (HTLV-1) was the first human retrovirus to be discovered and is the etiological agent of adult T-cell leukemia/lymphoma (ATLL), an aggressive T-cell malignancy with poor prognosis. HTLV-1 viral proteins interact with mechanisms and proteins present in host cells for their own benefit, evading the immune system and promoting the establishment of disease. Several viruses manipulate the autophagy pathway to achieve their infective goals, and HTLV-1 is not the exception. HTLV-1 Tax viral protein engages NF-κB and autophagy pathways prone favoring viral replication and T cell transformation. In this review we focus on describing the relationship of HTLV-1 with the autophagy machinery and its implication in the development of ATLL.